Essentials of clinical immunology - Chapel, Helen (`bLACKWELL, 2006)
Essential Clinical Immunology is aimed at clinical medical students and trainee doctors, although it will also appeal to medical professionals seeking a refresher in clinical immunology. The book provides the reader with the core information required to understand diseases with an immunological basis. This new edition of Essential Clinical Immunology is fully updated, now in full colour throughout and features: * coverage of the underlying pathophysiology and signs and symptoms of disease, as well as the special investigations required and management of patients; * emphasis on the clinical aspects with numerous real life case histories used to illustrate key concepts; * MCQs at the end of each chapter for self-assessment. Companion website An accompanying website, www.immunologyclinic.com, which includes: * Interactive multiple-choice questions for each chapter * A database of colour images from the book * A bank of case histories * References and further reading Reviews from previous edition: "This is a very comprehensive book, and would serve postgraduates well in addition to students embarking on pathology...It is well written by people who know their subject well, and know what information it is important to convey. ..All the vital areas you might want to read up on are covered more than adequately." MAD, The Student Magazine for Medics & Dentists at Bart's and the London "I think that this is the best of the bunch...much more relevant to our course and a sound investment for the future." Sphincter, Liverpool Medical Students' Society Magazine